Speech Interactions With Linguistic, Cognitive, and Visuomotor Tasks. - Dromey, Christopher; Bates, Emily (Journal of Speech, Language & Hearing Research, 2005)
Lip movements were examined across several repetitive speaking conditions (speech alone and speaking concurrently with a linguistic, cognitive, or visuomotor challenge task) in 20 young adults. Performance in these non-speech activities was also compared between isolated tasks and concurrent speech conditions. Linguistic challenges resulted in increased spatiotemporal variability of lip displacement across repetitions. Motor challenges led to more rapid speech with smaller lip displacement. These qualitatively different changes suggest that different aspects of attention are required for linguistic versus manual visuomotor activity. Vocal intensity increased for all concurrent task conditions compared with speech alone, suggesting increased effort compared to the control condition. Scores for linguistic performance decreased when utterance repetition occurred concurrently with the syntactic challenge. These findings reveal that speech motor activity can influence linguistic performance as well as be influenced by it. Although these data come from healthy speakers, they suggest that clinicians working with disordered speakers should not overlook the potential interactions among the demands of language formulation, cognitive activity, and speech motor performance. Reprinted by permission of the publisher.